'When I sing I use all my tools': Singing to infants as an expression of creativity in mothers. (1st December 2019) - Brisola, Elizabeth B. V.; Cury, Vera Engler; Davidson, Larry
When considering singing as an everyday creative activity in which people engage, investigations of children singing are more easily found than those of adults singing. Mothers commonly sing to their infants as part of caregiving, for the most part in the intimacy of their homes, perhaps making their creativity less visible to researchers. The purpose of this article is to address mothers' creative expression in singing to their infants and its implications on their psychological health. In order to do so, we first summarize knowledge derived from existing research literature pertaining to mothers' creativity in singing to their infants. A review of eleven selected texts revealed the following themes: mothers discovering their creativity, being spontaneous, being present, expressing themselves, adapting song material, using their own life experiences, and having fun. Although mothers do not necessarily consider themselves to be creative singers, they often invent lyrics and create melodies, add new verses to songs according to their particular child, and adapt the lyrics to each situation. They make use of their life experiences as they express their thoughts, feelings and perceptions through song. As they sing to their infant, they live in the present moment and instil meaning to their relationship in fun-filled interactions. We then discuss this musical creative expression in terms of mothers' psychological health. We propose that this musical activity contributes to mothers' health during the complex and transforming experience of motherhood, bringing satisfaction, relief and fulfilment, contributing to their personal growth as they move towards self-actualization, as described by humanistic psychology.